The Psychoanalytic Concept of Jouissance and the Kindling Hypothesis - Dimitriadis, Yorgos (Frontiers in Psychology, 2017)
This article aims to define the conceptual field of jouissance in Lacanian theory, and put forth the hypothesis of a relationship between certain neurophysiological mechanisms and specific clinical phenomena where jouissance is "kindled" and outside the control of the symbolic process. First, the author briefly introduces Lacan's notion of jouissance and the way it draws on Freud’s theorization, and describes the preliminary stages of this conceptual field in Lacan's work. Then, the jouissance related to two other concepts: repetition, with its Freudian and Lacanian nuances, as well as the – exclusively - Lacanian concept of the object petit a. Lacan's later conceptualization of language as jouissance (the notion of lalangue) is then discussed in relation to Freud's early ideas (“Letter 52”) on the different kinds of inscriptions that help form the mental apparatus. Finally, the author tries to formulate a hypothesis regarding specific neurophysiological mechanisms, based on clinical situations where jouissance becomes “kindled” and escapes the control of the symbolic processes through the neurophysiological mechanisms of conditioning, “kindling-sensitization” and “excitotoxicity”. In these cases, jouissance can have a destructive effect on the body and can affect, among others organs, the brain – a process the author has previously described heuristically as the “psychosomatic diseases of the brain”. This would be a special mechanism of automatism that would be triggered under the specific conditions of the fragility of the signifying chain (foreclosure of the Name-of-the-Father or solidification of the signifying chain) in combination with biological factors, including genetic factors. In this process, signifiers are reduced to signals, which in turn may be reduced to stimuli, with a tendency towards self-perpetuation, while affects are reduced to emotions and moods. Thus, conditioning and kindling-sensitization could also be understood in terms of a “semiotic reduction”. Can we therefore consider that certain phenomena of automatism and certain deficits (delusional moods, schizophrenic apathy, etc.) could be seen as psychosomatic disorders of the brain? The phenomena in question might also serve - albeit at random - as a kind of shield to mitigate excessive jouissance.